KEBERPIHAKAN TERHADAP PEREMPUAN DALAM PASTORAL KONSELING YESUS MENURUT INJIL YOHANES 8:1-11 - Jewadut, Jean Loustar; Rato, Gerald Chrislay; Asar, Fulgensius Prisaly (Lembaga Penelitian STKIP Widya Yuwana, 2023)
The purpose of writing this article is to explain the pastoral counseling strategy made by Jesus for women who were caught committing adultery and also for the Pharisees. The main idea of this article is Jesus’ partiality towards women as a week group in the face of the domination of the patriarchal culture of Jewish society which was instrumentalized by scribes and Pharisees. Taking sides with the weak is a form of Jesus’ pastoral counseling strategy according to the Gospel of John 8:1-11. The method used in this article is descriptive analysis using a literature and Bible text approach, namely the Gospel of John 8:1-11 to obtain a comprehensive explanation of the pastoral counseling strategy practiced by Jesus as a counselor. The theory used in this work is Biblical pastoral counseling, namely a type of pastoral counseling that uses the Word of God as the main reference in dealing with problems faced by counselees. Through an analysis of the Gospel of John 8:1-11, it appears that Jesus did pastoral counseling by paying attention to the context experienced and lived by the counselee. A good introduction to the context of the counselee makes Jesus able to deal with the problems experienced by the counselee.